Closed-Loop Two-Stage Stochastic Optimization of Offshore Wind Farm Collection System. Issue 4 (September 2020) - Pérez-Rúa, Juan-Andrés; Lumbreras, Sara; Ramos, Andrés; Cutululis, Nicolaos A.
Abstract: A two-stage stochastic optimization model for the design of the closed-loop cable layout of an Offshore Wind Farm (OWF) is presented. The model consists on a Mixed Integer Linear Program (MILP) with scenario numeration incorporation to account for both wind power and cable failure stochasticity. The objective function supports simultaneous optimization of: (i) Initial investment (network topology and cable sizing), (ii) Total electrical power losses costs, and (iii) Reliability costs due to energy curtailment from cables failures. The mathematical optimization program is embedded in an iterative framework called PCI (Progressive Contingency Incorporation), in order to simplify the full problem while still including its global optimum. The applicability of the method is demonstrated by application to a real-world instance. The results show the functionality of the model in quantifying the economic profitability when applying stochastic optimization compared to a deterministic approach, given certain values of cables failure parameters.